Automated Lung Region Segmentation in Pediatric Chest Radiography - Fonseca, Afonso Ueslei; Félix, Juliana de Paula; Vieira, Gabriel da Silva; Fernandes, Deborah; Soares, Fabrizzio (Revista de Informática Teórica e Aplicada, 2024)
In chest radiographs, the automatic identification of regions, structures, or objects that compose it can help the professional in the area to perform their reading and analysis more assertively, promoting the improvement and efficiency of the diagnosis. In the present work, we propose a method to segment the lung fields in pediatric chest radiographs (PCXR). Based on digital image processing operations and rules, the proposal is evaluated on a PCXR images dataset. The results are satisfactory for the different classes of images analyzed, indicating that the proposed method can be helpful in the preprocessing stages of more complex flows.